KEADAAN JALAN HUTAN DI HUTAN JATI DAN POTENSINYA DALAM AKSELERASI EROSI TANAH - DJaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1991)
An  inuestigation  on  forest  road conditiona  in teak forests  of  Cepu and Randublatung   Forest Districts and their soil erosion potentials  was conductild   in  early  1991.  The samples  of  roads  inuestigated  were  30  segments   in Cepu and  14 segments   in  Randublatung   each  of  60  m long.It  is found   that  from  the  total  of  266 km  truck  roads  in Cepu, only  3.7%  of  them  are in 2% are active roads. for the 180 km rail roads, 65.4% are in good conditionsIn Randublatung. the total  length of  truck  roads is 237  km  of  which  only  11.8%  are in good  conditiouns  but  78.3%  are active roads For rail roads, the total length is only  33 km  and only  13.5% of  them are in good  conditionsThe total  area used for road infrastructures (combined   truck  and  rail roads)  in cepu  and Randublatung   are 266  ha (0;8%) and 163 ha  (8.5%), respectively. This means that an average land lost due  to roading is 0. 7%.All  factors in the  USLE  for  the  teak forest  areas of  Cepu  and Randublatung are in the level of low  scores in terms of  soil erosion  acceleration  potentials  except   soil erodibility.   It is  noticed  in the field  that this soil erodibility factor is couered  by other  dominant facton   and. therefore,  soil  erosion potentials  of  forest roads roads are generally low.